The Influence of Workload and Work Environment on Employee Performance at the Regional Civil Service Agency (BKD) of Patent District, West Lombok: Pengaruh Beban Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Badan Kepegawaian Daerah (BKD) Kabupaten Paten Lombok Barat - Nedya Safitri Utami Nedya Safitri Utami; Zainal Abidin; Mukmin Suryatni (J-MARK (Jurnal Manajemen Risiko dan Keuangan), 2023)
This study entiled the effect of Work (X1) and Work Environment on Employee Performance at the Regional Personal Agency (BKD) of West Lombok Regency. The purpose of this study was to determine the effect of workload and work environment on employee performance at the Regional Personal Agency (BKD) Office of West Lombom Regency. The type of research used is casual associative research with quantitative approach techniques. The data collection method is through the census method using primary data collected directly from respondents through questionnaires. Respondents used in this study were all BKD employees of West Lombok Regency, totaling 50 employees. The data analysis tool used in this study is multiple linear regression analysis using the SPSS version 21 program. The results of the study show that : (1) Workload has a negative and significant effect on employee performance. (2)The work environment has a positive and significant effect on employee performance. (3) The environment has a dominant influence on employee performance.